Women, Life, Freedom Our Fight for Human Rights and Equality in Iran - Sotoudeh, Nasrin (Brown Democracy Medal, 2023)
The Laurence and Lynne Brown Democracy Medal, presented by the McCourtney Institute for Democracy at Penn State, recognizes outstanding individuals, groups, and organizations that produce innovations to further democracy in the United States or around the world. Nasrin Sotoudeh is an Iranian lawyer and human rights activist who has been called ""Iran's Nelson Mandela."" Sotoudeh is a longtime opponent of the death penalty, advocate of improving imprisonment health conditions, and an activist dedicated to fighting for the rights of women, children, religious and ethnic minorities, journalists and artists, and those facing execution. As a result of her advocacy, Sotoudeh has been repeatedly imprisoned by the Iranian government for crimes against the state; she served one sentence from 2010 to 2013 and was sentenced again in 2018 to thirty-eight years and six months in prison and 148 lashes. Her work has been featured in the 2020 documentary Nasrin, by filmmakers Jeff Kaufman and Marcia S. Ross. For this important work, she is the recipient of the 2023 Brown Democracy Medal from the McCourtney Institute for Democracy, marking the award's tenth year.